Sustentabilidade e Agronegócio: Ferramentas Adotadas em Localidades Rurais em Codó-MA - Alves, Caline Silva (2024)
The environmental impacts caused by agribusiness are highly harmful, compromising the quality of human life, fauna, and flora. Sustainability is crucial for maintaining the natural resources essential for life. The problem lies in the destruction caused to vegetation to make room for agribusiness. In a chaotic planet, crying out for help, measures need to be taken. With this in mind, the present research aims to identify the applicability of sustainability in agribusiness in rural areas in the city of Codó-MA, as well as analyze the management techniques performed there, making it possible to describe the sustainable practices adopted in local agriculture, along with their respective challenges and opportunities, aiming to understand in a general sense, what the vision of Codó farmers is regarding sustainability in the field. For this study, a field research with a qualitative and exploratory approach was conducted, where a questionnaire with open-ended questions was applied, obtaining 8 (eight) respondents and 2 (two) interviewees. It was concluded that the use of methods inclined towards sustainable development within the field varies according to the challenges and opportunities faced by rural producers, just as the scarcity of resources directly interferes with the management of the represented crops here.